Enhancing Combustion Characteristics of Callophyllum Inophyllum Fuel Using Magnetic Fields - Imam Rudi Sugara; Dani Hari Tunggal Prasetiyo (ENERGY: JURNAL ILMIAH ILMU-ILMU TEKNIK, 2025)
The challenges of energy security and environmental sustainability have driven the development of eco-friendly alternative fuels, among which second-generation biodiesel has gained significant attention. This study aims to analyze the combustion quality of biodiesel derived from Calophyllum inophyllum oil (CIME) under the influence of an external magnetic field on the laminar flame speed in a premixed flame system. CIME biodiesel was produced through a transesterification process following degumming and esterification stages. Experimental tests were conducted using a stainless-steel Bunsen burner with a T-junction configuration and integrated heating system, in which magnetic fields with strengths ranging from 7000 to 10000 gauss were applied directly to the flame region. The equivalence ratio (ϕ) of the fuel-air mixture was varied between 0.4 and 1.4. Laminar flame speed was calculated from flame visualization data based on the observed flame angle. The results indicate that the magnetic field significantly enhanced the laminar flame speed, with the highest value observed at ϕ = 0.8 and a magnetic field strength of 10000 gauss. This phenomenon is attributed to the increased oxygen concentration in the reaction zone, induced by the magnetic attraction of paramagnetic O₂ molecules. These findings suggest that the integration of magnetic fields into biodiesel combustion processes can potentially improve energy efficiency and reduce emissions, offering an innovative approach for advancing renewable energy systems.